+0  
 
0
274
2
avatar+564 

chilledz3non  Jun 17, 2015

Best Answer 

 #1
avatar+78750 
+13

2 - 12/(4 - x)  = (2x + 4) / (x^2 - 16)   we can rewrite this as

 

2 + 12/(x - 4)   = 2(x + 2)/ [(x - 4) (x + 4) ]        multiply through by [(x - 4) (x + 4) ]

 

2 [(x - 4) (x + 4) ] + 12(x + 4)  = 2(x + 2)        divide thrrough by 2

 

[(x - 4) (x + 4)] + 6(x + 4)  = x + 2    simplify

 

x^2 - 16 + 6x + 24  =  x + 2   

 

x^2 + 6x + 8   = x + 2

 

x^2 + 5x + 6    =  0      factor

 

(x + 3) (x + 2)  = 0      and setting each factor to 0 we have x = -2   or  x = -3 

 

{There are no extraneous solutions }

 

 

CPhill  Jun 17, 2015
Sort: 

2+0 Answers

 #1
avatar+78750 
+13
Best Answer

2 - 12/(4 - x)  = (2x + 4) / (x^2 - 16)   we can rewrite this as

 

2 + 12/(x - 4)   = 2(x + 2)/ [(x - 4) (x + 4) ]        multiply through by [(x - 4) (x + 4) ]

 

2 [(x - 4) (x + 4) ] + 12(x + 4)  = 2(x + 2)        divide thrrough by 2

 

[(x - 4) (x + 4)] + 6(x + 4)  = x + 2    simplify

 

x^2 - 16 + 6x + 24  =  x + 2   

 

x^2 + 6x + 8   = x + 2

 

x^2 + 5x + 6    =  0      factor

 

(x + 3) (x + 2)  = 0      and setting each factor to 0 we have x = -2   or  x = -3 

 

{There are no extraneous solutions }

 

 

CPhill  Jun 17, 2015
 #2
avatar+564 
+10

Thank you CPhill!

chilledz3non  Jun 17, 2015

13 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details